Question
Asked Oct 10, 2019
x = −3y2
 


Label the x- and y-intercepts. (If an answer does not exist, enter DNE.)

x-intercept = 

y-intercept =

check_circleExpert Solution
Step 1
Consider the given function as x -3y*.
=_
Substitute y 0 in x=-3y^ to find the x-intercept as follows
-3y0
0
=
y 0
The x-intercept is (0,0)
help_outline

Image Transcriptionclose

Consider the given function as x -3y*. =_ Substitute y 0 in x=-3y^ to find the x-intercept as follows -3y0 0 = y 0 The x-intercept is (0,0)

fullscreen
Step 2
Substitute x 0 in x=-3y^ to find the y-intercept
as follows
--3(0)
x=3(0)
The y -intercept is (0.0)
help_outline

Image Transcriptionclose

Substitute x 0 in x=-3y^ to find the y-intercept as follows --3(0) x=3(0) The y -intercept is (0.0)

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour*

See Solution
*Response times may vary by subject and question
Tagged in

Math

Algebra

Other

Related Algebra Q&A

Find answers to questions asked by student like you

Show more Q&A add